before 3 years the sum of the age of father and son is 59 then before 5 years the sum of theirs age was
Answers
Answered by
8
Let,
Father's age =
years
Son's age =
years
Three years ago, their ages will be –
Father's age = ( x - 3 ) years
Son's age = ( y - 3 ) years
A.T.Q.
x - 3 + y - 3 = 59
x + y - 6 = 59
x + y = 59 + 6
x + y = 65
![<u>Father's age + Son's age = 65</u> <u>Father's age + Son's age = 65</u>](https://tex.z-dn.net/?f=%26lt%3Bu%26gt%3BFather%27s+age+%2B+Son%27s+age+%3D+65%26lt%3B%2Fu%26gt%3B)
Now before 5 years, their age will be –
Father's age = ( x - 5 ) years
Son's age = ( y - 5 ) years
Their sum -
= ( x - 5 ) + ( y - 5 )
= x + y - 10
= 65 - 10
=![<b>55</b> <b>55</b>](https://tex.z-dn.net/?f=%26lt%3Bb%26gt%3B55%26lt%3B%2Fb%26gt%3B)
Father's age =
Son's age =
Three years ago, their ages will be –
Father's age = ( x - 3 ) years
Son's age = ( y - 3 ) years
A.T.Q.
x - 3 + y - 3 = 59
x + y - 6 = 59
x + y = 59 + 6
x + y = 65
Now before 5 years, their age will be –
Father's age = ( x - 5 ) years
Son's age = ( y - 5 ) years
Their sum -
= ( x - 5 ) + ( y - 5 )
= x + y - 10
= 65 - 10
=
kitty9852:
-3-3= -6
Similar questions
Physics,
8 months ago
Math,
8 months ago
Social Sciences,
8 months ago
Math,
1 year ago
Math,
1 year ago